Modeling the talent shortage in Malaysian Islamic banking institutions - Mohd Ikhwan Aziz
Generally, the first implicit assumption of the increasing number of talent supply and demand should minimise the talent shortage issue in the Islamic banking institutions (IBIs). However, the situation was contradicting in IBIs and left the circumstanO? remains in paradox, that caused an acute talent shortage. Nevertheless, the number of talent supply in Islamic banking education institutions (IBEls) and talent demand in IBIs gradually increase every year. Thus, which parties are held responsible for . s c ndition, is it talent, IBIs, IBEls, or the government? Therefore, the purpose of ~'his study is to identify the affecting factors in the talent shortage in Malaysian IBIs. N t, to analyse the effect of the factors towards talent shortage in Malaysian fBI .. Fina ey, to develop a talent development model for talent shortage in Mala sian IBIs. Further, through the extensive re iews ofth literature with various f urces, it has formed a conceptual framework m del calle 0 talent development model for talent shortage in Malaysian IBIs. The built model s displayed the correlation relationship between talent shortage and talent md aIid supply variables. The researcher used a mixed method approach that comprises exp 'ration, description and explanatory characteristic, in which it is the combinatlorr of qcr titative and qualitative method approaches. Then, questionnaires were dispensed to 380 Islamic banking and finance students in Malaysian public universities for quantitative method approach. While for qualitative method approach, an in-depth interview method used by having interview session with nine experts from IBIs. The data gathered from the questionnaires were analysed by structural equation modelling (SEM) with IBM-SPSS (Statistical Package for the Social Science) and IBM-AMOS (Analysis of a Moment Structure) software to generate the quantitative result. Meanwhile, qualitative data gathered from face-to-face and semi-structure interview were analysed through constant comparative method with ATLAS.ti to generate the qualitative result. After triangulation process, the researcher found the significant critical value of talent supply towards talent shortage in Malaysian IBIs. Concurrently, curriculum variable displayed a dominant effect on the talent supply. Furthermore, research hypothes s of talent demand and supply were accepted with highly significant towards the determine vari le of talent shortage. Moreover, it has displayed that talent demand andsupply variab es give a dominant impact to the talent shortage in IBIs. In continuation, the developed mo of talent development have been validated through fitness indexes and endorsed by three experts. Overall, the research findings showed that curriculum factor play an important role towards talent shortage in IBIs. Although the availability of curriculum development is enough through a comprehensive education system, but the curriculum could not guaranteed the talent for . ob market. The results of this study have provide significant contributions to field of tal nt de 0 nt in IBIs and IBEls either from the theoretical or the empirical aspect. The researchi offered unique insights talent development model through integrated model wi e primary objective of balancing the labour market between talent supply and demand.